How should anti-hypertensive medications be adjusted before screening for primary aldosteronism? - Jin-Ying Lu; Yi-Yao Chang; Ting-Wei Lee; Ming-Hsien Wu; Zheng-Wei Chen; Yen-Ta Huang; Tai-Shuan Lai; Leay Kiaw Er; Yen-Hung Lin; Vin-Cent Wu; Hao-Min Cheng; Hsien-Li Kao; et al. (Journal of the Formosan Medical Association, 2024)
Anti-hypertensive medications may affect plasma renin activity and/or plasma aldosterone concentration, misleading the interpretation of the aldosterone-to-renin ratio when screening for primary aldosteronism. The Task Force of Taiwan PA recommends that, when necessary, using α-adrenergic receptor blocking agents, centrally acting α-adrenergic agonists, and/or non-dihydropyridine calcium channel blockers should be considered to control blood pressure before screening for PA. We recommend temporarily holding β-adrenergic receptor blocking agents, mineralocorticoid receptor antagonists, dihydropyridine calcium channel blockers, angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, and all diuretics before screening for PA. Further large-scale randomized controlled studies are required to confirm the recommendations.